El sistema concursal frente a la COVID-19: el caso peruano - De la Puente, Carlos (2023)
The purpose of this article is to evaluate how useful the Accelerated Bankruptcy Refinancing Procedure (PARC) could be to mitigate the effects of the COVID-19 pandemic, and to identify the contributions that its implementation could bring to the Peruvian bankruptcy system. The government strategy applied to protect the economic sectors from the consequences of COVID-19 had two lines of action: the creation of Reactiva Perú and the implementation of a speedy bankruptcy procedure called PARC. Given its design, and thinking more about the medium term, it aspires to identify the contributions that its implementation could bring to the Peruvian bankruptcy system, which could be considered in an upcoming reform of the bankruptcy regulation.